2016
DOI: 10.1007/s11096-016-0258-9
|View full text |Cite
|
Sign up to set email alerts
|

Information on actual medication use and drug-related problems in older patients: questionnaire or interview?

Abstract: Background Information on medication use and drug-related problems is important in the preparation of clinical medication reviews. Critical information can only be provided by patients themselves, but interviewing patients is time-consuming. Alternatively, patient information could be obtained with a questionnaire. Objective In this study the agreement between patient information on medication use and drug-related problems in older patients obtained with a questionnaire was compared with information obtained d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
(25 reference statements)
0
14
0
1
Order By: Relevance
“…The occurrences of all drug-related problems resemble what reported by Kjeldsen, LJ et al [10] The perceptions of occurrences of medication errors of nurses almost the same or little lower than what reported by You, M et al [11] The perceptions of occurrences of adverse drug reaction and drug non-compliance was higher than what reported by Willeboordse, F et al That's related absent of patient medications counseling and program at healthcare organizations and week health knowledge with emphasis on the medicines information, with lower number of clinical pharmacist to reduce or stop those problems. [6] The most drug-related problems knowledge gained from the internet and drug leaflet and last resources were healthcare professionals because there are not patient medications education programs or drug-related problems follow up the system at Ministry of health hospitals. The knowledge and perception of drugrelated problems are not appropriate that may lead to void prevent those problems and the consequences of complications with the high economic burden on healthcare system at hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrences of all drug-related problems resemble what reported by Kjeldsen, LJ et al [10] The perceptions of occurrences of medication errors of nurses almost the same or little lower than what reported by You, M et al [11] The perceptions of occurrences of adverse drug reaction and drug non-compliance was higher than what reported by Willeboordse, F et al That's related absent of patient medications counseling and program at healthcare organizations and week health knowledge with emphasis on the medicines information, with lower number of clinical pharmacist to reduce or stop those problems. [6] The most drug-related problems knowledge gained from the internet and drug leaflet and last resources were healthcare professionals because there are not patient medications education programs or drug-related problems follow up the system at Ministry of health hospitals. The knowledge and perception of drugrelated problems are not appropriate that may lead to void prevent those problems and the consequences of complications with the high economic burden on healthcare system at hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…It seldom to find a study to explore drug-related problems healthcare professionals and patient attitudes perspectives in Saudi Arabia or Gulf and Middle East counties or even worldwide. [6] The objective of the study to explore the drug-related problems healthcare professionals and patient attitudes in Kingdom of Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…Although using PROMISE within CMRs had no detectable effect on the number of DAS at follow-up, we believe that the PROMISE instrument could be useful to draw the attention of healthcare professionals to common DAS as symptom management is a cornerstone of care for patients with chronic conditions [ 39 ]. Furthermore, Willeboordse et al [ 40 ] reported that except for vulnerable patients (characterized by > 4 chronic diseases, > 10 drugs used, and low health literacy) a questionnaire may be as effective as an interview in determining the patient perspective. Hence, the use of PROMISE may improve the feasibility of a CMR as a replacement for or in support of the patient interview.…”
Section: Discussionmentioning
confidence: 99%
“…), over eerdere ervaringen met geneesmiddelen en over ervaren bijwerkingen. Deze informatie kan verkregen worden tijdens een consult, of door het gebruik van een vragenlijst [17]. Maar ook in de laatste fase van de medicatiebeoordeling, als het behandelplan wordt besproken en afspraken gemaakt worden over het medicatieregime, zijn betrokkenheid en instemming van de patiënt essentieel.…”
Section: Overwegingen Bij De Medicatiebeoordelingunclassified